Validation of spot-testing kits to determine iodine content in salt - Chandrakant S. Pandav; Narendra K. Arora; Anand Krishnan; Rajan Sankar; Smita Pandav; Madhu G. Karmarkar (The World Health Organization, 2000)
Iodine deficiency disorders are a major public health problem, and salt iodization is the most widely practised intervention for their elimination. For the intervention to be successful and sustainable, it is vital to monitor the iodine content of salt regularly. Iodometric titration, the traditional method for measuring iodine content, has problems related to accessibility and cost. The newer spot-testing kits are inexpensive, require minimal training, and provide immediate results. Using data from surveys to assess the availability of iodized salt in two states in India, Madhya Pradesh and the National Capital Territory of Delhi, we tested the suitability of such a kit in field situations. Salt samples from Delhi were collected from 30 schools, chosen using the Expanded Programme on Immunization (EPI) cluster sampling technique. A single observer made the measurement for iodine content using the kit. Salt samples from Madhya Pradesh were from 30 rural and 30 urban clusters, identified by using census data and the EPI cluster sampling technique. In each cluster, salt samples were collected from 10 randomly selected households and all retailers. The 15 investigators performing the survey estimated the iodine content of salt samples in the field using the kit. All the samples were brought to the central laboratory in Delhi, where iodine content was estimated using iodometric titration as a reference method. The agreement between the kit and titration values decreased as the number of observers increased. Although sensitivity was not much affected by the increase in the number of observers (93.3% for a single observer and 93.9% for multiple observers), specificity decreased sharply (90.4% for a single observer and 40.4% for multiple observers). Due to the low specificity and resulting high numbers of false-positives for the kit when used by multiple observers (''real-life situations''), kits were likely to consistently overestimate the availability of iodized salt. This overestimation could result in complacency. Therefore, we conclude that until a valid alternative is available, the titration method should be used for monitoring the iodine content of salt at all levels, from producer to consumer, to ensure effectiveness of the programme.